Social Justice Based on Religious Forms of Prosociality in Russia - Kislyakov, Pavel A.; Shmeleva, Elena A.; Sergeev, Sergey E.; Kulikov, Sergey B. (International Journal of Criminology and Sociology, 2022)
This article shows the social and psychological aspects of the prosociality in Russia which help to see the ways to social justice forming. In Russia, under the influence of Christianity forms an approach to prosocial behavior as a mandatory element of public life. Objective of study is an identification of the peculiarities of prosocial manifestation in Russian people with different levels of religiosity in modern social and cultural conditions. This study is conducted on the base of the complex of methods, namely, The Scale of Altruism (SRA); Social Norms of Prosocial Behavior (SNPB); Index of Core Spiritual Experiences (INSPIRIT); Religious Orientation Scale (RSO). The sample consists of 221 people living in various Russian cities (38% of men, 62% of women) aged 20 to 66 years (M-39.8). As a result, the collected data and their evaluation and discussion help to support the idea that spirituality and citizenship have a regulatory influence on the prosocial motives of mercy, tolerance, and altruism.